Are Economic Growth and Sustainable Development Converging? Evidence from the Comparable Genuine Progress Indicator for Organisation for Economic Co-operation and Development Countries - Pais, Daniel Francisco; Afonso, Tiago Lopes; Marques, AntÃ³nio Cardoso; Fuinhas, JosÃ© A (International Journal of Energy Economics and Policy, 2019)
Academic literature has reflected increasing concerns about the trade-off between preserving the environment and economic growth. To address these concerns, new measurements are needed to evaluate sustainable development, given the limitations of Gross Domestic Product (GDP) in quantifying welfare and sustainability. Genuine Progress Indicator (GPI) is one of those alternative measurements. This paper assesses sustainable development for 28 OECD countries by computing a comparable GPI. Two different approaches to economic growth and sustainable development are discussed. Results suggest that the richest countries are not always the most sustainable. Furthermore, the effect of the financial crisis is verified immediately in the GDP, in contrast to the lagged effect observed in the GPI. Additionally, measures that promote economic growth may not improve sustainability, and may even negatively affect it. Consequently, alternative indicators such as the CGPI can obtain more valuable information for policy-makers seeking to achieve both economic growth and sustainable development. Keywords: CGPI; sustainable development; economic growth JEL Classifications: Q01; Q51; Q56 DOI: https://doi.org/10.32479/ijeep.7678